Broad Bean (Vicia faba L.) Induces Intestinal Inflammation in Grass Carp (Ctenopharyngodon idellus C. et V) by Increasing Relative Abundances of Intestinal Gram-Negative and Flagellated Bacteria - Li, Zhifei; Yu, Ermeng; Wang, Guangjun; Yu, Deguang; Zhang, Kai; Gong, Wangbao; Xie, Jun (Frontiers in Microbiology, 2018)
Constant consumption of broad bean (Vicia faba L.) induces intestinal inflammation and reduces growth rate in grass carp (Ctenopharyngodon idellus C. et V). However, the mechanisms underlying these effects are unclear. In mammalian models of inflammatory bowel disease (IBD), endotoxin and flagellin cause intestinal inflammation through upregulation of tumor necrosis factor (TNF)-α expression. We therefore speculated that broad bean consumption alters intestinal microbiota composition, thereby increasing the relative abundance of endotoxin-producing Gram-negative and flagellated bacteria and resulting in upregulation of TNF-α and intestinal inflammation in grass carp. We tested this hypothesis by comparing intestinal microbiota compositions of grass carp fed broad bean (GCBB), hybrid giant napier (Pennisetum sinese Roxb, GCHG), or formula feed (GCFF) by 16S rRNA gene sequencing. We also performed a histological analysis of the intestinal inner wall by scanning electron microscopy and measured intestinal wall and serum concentrations of TNF-α. Our results revealed epithelial cell damage including microvillus effacement and synechia along with increased TNF-α levels in the intestinal wall in the GCBB group as compared to the GCHG and GCFF groups. The relative abundances of Gram-negative and flagellated bacteria were also higher in the GCBB group than in the GCHG and GCFF groups; this was accompanied by upregulation of genes expressing endotoxin and flagellin in intestinal microbiota. Thus, broad bean-induced intestinal inflammation in grass carp shares features with IBD. Our findings demonstrate that the microbiome in fish is directly influenced by diet and provide a reference for deconstructing host–intestinal microbiota interactions.